SEASONAL VARIATIONS IN THE POPULATION OF FRESHWATER SHRIMP Palaemon elegans DECAPODA : PALAEMONIDAE IN CERTAIN SITES IN THE NAJAF SEA - AL-MOSAWI, HASANEN SAHIB MAHDI; TAHA, THAER MAHMOOD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Aims: This study was conducted in four selected sites from the bahr al-najaf depression for the period from 2020-2021 for the purpose of evaluating some of the chemical and physical characteristics and their monthly changes and their relationship with the main groups of the benthic invertebrate community, including rock shrimp. Study Design: The study showed a difference in the density of rock shrimp from one site to another, where the rock shrimp community recorded a population density that ranged between ( 2133.33-88.88) individuals/m2. Place and Duration of Study: The rock shrimp Palaemon elegans was recorded in this study for the first time in the bahr al-najaf depression, Methodology: In order to determine the significant differences of the benthic organisms, the average monthly densities were calculated in the study sites (4 sites), where the highest significant difference was recorded in the first site at (P < 0.05), and it was in July (LSD = 273.53) for the most important benthic organisms, which were found in a density that exceeded the other benthic organisms, which is rock shrimp, while the least significant difference was recorded for rock shrimp for all sites in the month of May, which is within the summer season, where it was (LSD = 26.18) at (P < 0.05). Results: The results showed that site_1 of the study (in site_1 ) is the most densely populated shrimp, where the annual average density was (277,129) individuals/m2 compared with other sites, and the highest population density for shrimp was recorded in August 2020 and it was (711.111) individuals/m2, While the lowest annual rate of population density was recorded in site_4, which amounted to (107.407) individuals/m2, while the average population density was recorded at 29.629 individuals/m2 in the months (November, December, January) at (P < 0.05). Conclusion: This study recorded a highly significant correlation between BOD5 and the population density of shrimp in site_2 and it was (r = * 0.78) at (P˂0.05), while the same site recorded a significant negative correlation of nitrate with the population density of rock shrimp (r = * - 0.77).